Smart cities e corporações: novas feições do governo de populações - Branco, Priscilla Alves Teixeira [UNIFESP] (2019)
Since the early 2000s companies known as "tech giants" have significantly directed their operations to expand their "smart city" business division. Such action has placed these companies as important players with influence in all levels of government. Hence, the research analyzed the commercial proposals of Smart Cities offered by IBM and Microsoft and its relations to the emergence of new forms of power regimes, social control and the reconfigurations of the government of the populations. Thus, we will discuss the expansion of these proposals in urban management considering that their development, control and application will occur in environments technically mediated by these large corporations.